Changes in Muscle Fiber Characteristics Due to Resistance and Endurance Training Programs in Sports Coaching Education Students at UPRI - Abd. Haris; Nurul Octaviani Basri; Charmila Tandi Rerung; Siti Nurhalizah Mutia Aulria (Universitas Pejuang Republik Indonesia, 2025)
Background: Muscle fiber composition is a fundamental determinant of physical performance and athletic potential. Systematic training programs, particularly resistance and endurance training, are known to induce distinct adaptations in Type I (slow-twitch) and Type II (fast-twitch) muscle fibers at morphological, metabolic, and molecular levels. Objectives: This study aimed to analyze changes in muscle fiber characteristics including cross-sectional area (CSA), myosin heavy chain (MHC) isoform expression, and oxidative enzyme activity following 12 weeks of structured resistance and endurance training programs in Sports Coaching Education students at Universitas Pejuang Republik Indonesia (UPRI). Methods: A quasi-experimental design with pre-test and post-test was applied to 40 male students (aged 18–22 years) randomly assigned to resistance training (RT, n=20) or endurance training (ET, n=20) groups. Physical performance tests (1RM bench press, VO₂max beep test, vertical jump, and 30-meter sprint) were conducted before and after the 12-week intervention. Muscle fiber adaptation indicators were assessed via isokinetic dynamometry and functional indirect markers. Results: The RT group demonstrated significant increases in Type II fiber hypertrophy indicators (CSA estimated via ultrasound), maximum strength (1RM +23.4%), and explosive power (vertical jump +18.7%). The ET group showed improvements in aerobic capacity (VO₂max +16.2%), muscular endurance, and fatigue resistance consistent with a shift toward Type I fiber dominance. Conclusions: A 12-week structured training program produces distinct muscle fiber adaptations depending on modality. Resistance training promotes Type II fiber characteristics, while endurance training enhances Type I fiber qualities. These findings provide evidence-based guidance for program design in sports coaching education curricula.